Students’ perception of online communication language learning through Instagram - Malikhatul Lailiyah; Lian Agustina Setiyaningsih (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
The use of Social Media has become pervasive. As an educator, this might facilitate the learning experiences, especially for second language learning. Bring that issues, this study intended to delve into students' perception regarding their experience in using mobile-assisted language learning (MALL) tools especially Instagram for speaking activity in English for Specific Purposes class. Besides, this study also explored students' opinions regarding the use of Instagram for language learning purposes. Two sets of questionnaires were distributed and analyzed. The result indicated that the participants expressed a positive perception of the use of Instagram for learning language purposes. The finding revealed that, among the participants, Instagram is the most popular social media. The positive students’ perception is that learning through Instagram is effective because it provides a new way of learning language and it accelerates interactive vocabulary enrichment.  DOI: 10.26905/enjourme.v5i2.5202